Comparisons between sluggish cognitive tempo and ADHD-restrictive inattentive presentation phenotypes in a clinical ADHD sample - Unsel-Bolat, Gul; Ercan, Eyup Sabri; Bolat, Hilmi; Suren, Serkan; Bacanli, Ali; Yazici, Kemal Utku; Rohde, Luis Augusto (Springer Wien, 2019)
There is a debate how different ADHD cases with a comorbid sluggish cognitive tempo (SCT) phenotype are from subjects with a pure inattentive ADHD presentation (ADHD-restrictive inattentive presentation). In this study, 214 patients aged 8-15 years from an ADHD outpatient clinic were assessed, and 100 typically developing controls (TD) were recruited as comparisons. No psychiatric comorbidities except for oppositional defiant disorder were allowed. We compared 29 cases with ADHD + SCT with 34 ADHD-RI cases and 92 TD subjects on sociodemographic profiles, CBCL subscales scores and neurocognitive findings. Regarding sociodemographic profiles (age, gender and parental education) and CBCL subscales, ADHD + SCT and ADHD-RI cases did not differ in any score (all p > 0.05). Comparing with SCT cases, ADHD-RI cases presented slower psychomotor speed and worse neurocognitive index (p < 0.001). We found that only SCT was independently associated with a lower performance in total memory score. ADHD-RI was independently associated with longer reaction time. Our findings suggest that although SCT might be expected to present longer reaction time, we found that slower psychomotor speed and longer reaction time scores were related to inattention. Overall, SCT and ADHD-RI groups were distinguished by differential associations with measures of memory and reaction time.
Keywords: Sluggish cognitive tempo; ADHD; Inattention; Neurocognitive profile; Slow psychomotor speed